Kann die Ketoacidose bei pädiatrischen Patienten mit Manifestation eines Diabetes mellitus Typ 1 vermieden werden? Lehren aus der COVID-19-Pandemie - Mönkemöller, Kirsten; Kamrath, Clemens; Hammersen, Johanna; Biester, Torben; Warncke, Katharina; Pappa, Angeliki; Fink, Katharina; Raile, Klemens; Rohrer, Tilman R.; Holl, Reinhard W. (Monatsschrift Kinderheilkunde, 2021)
Background: Diabetic ketoacidosis (DKA) is a life-threatening emergency in children and adolescents with manifestation of type 1 diabetes mellitus (DM1) and often associated with delayed diagnosis or previous diagnostic errors. During the coronavirus disease 2019 (COVID-19) lockdown period in Germany, less patients presented at emergency departments and private practices. Objective: The aim of this study was to investigate the DKA risk in children and adolescents with DM1 manifestation during the COVID-19 lockdown and associated risk factors. Material and methods: The frequency of DKA at DM1 onset in patients <18 years between 13 March and 13 May 2020 in pediatric diabetes centers was analyzed. The centers also documented their assessment, if the presentation was delayed or the diagnosis was not made on the first medical consultation. In order to analyze the influence of the risk factors on the frequency of DKA, the data from 2020 were compared with the same periods in 2018 and 2019 using multivariable linear and logistic regression. Results: The data of 532 patients from 216 diabetes centers showed that the risk for DKA increased by 84.7% and the risk for severe DKA increased by 45.3% compared to the years 2018/2019. Children <6 years had the highest risk with an 141.6% increase for DKA and 97.0% for severe DKA compared to the previous years. Migration background was a risk factor independent of COVID-19. Of the patients 31% had either a delayed presentation or a missed diagnosis. Conclusion: During the COVID-19 lockdown the frequency of DKA and severe DKA at DM1 onset was significantly increased for children and adolescents in Germany. Age <6 years, migration background and delayed diagnosis were the main risk factors.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Children < 6 years; COVID-19 lockdown; Delayed presentation; Migration background; Missed diagnosis